Snow chemistry across Antarctica - Bertler, N.; Mayewski, Paul Andrew; Aristarain, A.; Barrett, P.; Becagli, S.; Bernardo, R.; Bo, S.; C, Xiao; Curran, M.; D, Qin; Dixon, D.; Ferrona, F.; et al. (Annals of Glaciology, 2005)
An updated compilation of published and new data of major-ion (Ca, Cl, K, Mg, Na, NO3, SO4) and methylsulfonate (MS) concentrations in snow from 520 Antarctic sites is provided by the national ITASE (International Trans-Antarctic Scientific Expedition) programmes of Australia, Brazil, China, Germany, Italy, Japan, Korea, New Zealand, Norway, the United Kingdom, the United States and the national Antarctic programme of Finland. The comparison shows that snow chemistry concentrations vary by up to four orders of magnitude across Antarctica and exhibit distinct geographical patterns. The Antarctic-wide comparison of glaciochemical records provides a unique opportunity to improve our understanding of the fundamental factors that ultimately control the chemistry of snow or ice samples. This paper aims to initiate data compilation and administration in order to provide a framework for facilitation of Antarctic-wide snow chemistry discussions across all ITASE nations and other contributing groups. The data are made available through the ITASE web page (http://www2.umaine.edu/itase/content/syngroups/snowchem.html) and will be updated with new data as they are provided. In addition, recommendations for future research efforts are summarized.
Keywords: Antarktis; geovitenskap; glasiokjemi; glasiologi; iskjerner; transantarktiske ekspedisjoner

The International Trans-Antarctic Scientific Expedition (ITASE): an overview - Mayewski, Paul Andrew; Frezzotti, Massimo; Bertler, Nancy; Ommen, Tas V. A. N.; Hamilton, Gordon; Jacka, Tim H.; Welch, Brian; Frey, Markus; Dahe, Qin; Jiawen, Ren; Simões, Jefferson; Fily, Michel; et al. (Annals of Glaciology, 2005)
From its original formulation in 1990 the International Trans-Antarctic Scientific Expedition (ITASE) has had as its primary aim the collection and interpretation of a continent-wide array of environmental parameters assembled through the coordinated efforts of scientists from several nations. ITASE offers the ground-based opportunities of traditional-style traverse travel coupled with the modern technology of GPS, crevasse detecting radar, satellite communications and multidisciplinary research. By operating predominantly in the mode of an oversnow traverse, ITASE offers scientists the opportunity to experience the dynamic range of the Antarctic environment. ITASE also offers an important interactive venue for research similar to that afforded by oceanographic research vessels and large polar field camps, without the cost of the former or the lack of mobility of the latter. More importantly, the combination of disciplines represented by ITASE provides a unique, multidimensional (space and time) view of the ice sheet and its history. ITASE has now collected >20 000km of snow radar, recovered more than 240 firn/ice cores (total length 7000 m), remotely penetrated to ~4000m into the ice sheet, and sampled the atmosphere to heights of >20 km.
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; geovitenskap; glasiologi; klimatologi; transantarktiske ekspedisjoner

Effort explores 130 Million years of Antarctic paleoenvironment - Kristoffersen, Yngve; Goodwin, Ian D; Cooper, Alan K (Eos, Transactions American Geophysical Union, 2000)
Antarctic climate history has been dominated by events and turning points with causes that are poorly understood. To fill the gaps in our knowledges new effort is underway in the international geologic community to acquire and coordinate the circum-Antarctic geologic data needed to derive and model paleoenvironments of the past 130 m.y. The effort, which focuses principally on using shallow (<100 m) stratigraphic drilling and coring to acquire the geologic data, is being led by the Antarctic Offshore Stratigraphy Project (ANTOSTRAT), a group that works under the aegis of the Scientific Committee on Antarctic Research (SCAR). About 40 scientists from 12 countries met this past summer in Wellington, New Zealand, at an ANTOSTRAT meeting to discuss strategies for implementing the desired paleoenvironmental field and modeling studies. The meeting was held in conjunction with the 8th International Symposium on Antarctic Earth Sciences.
Keywords: Antarktis; geologi; geovitenskap; klimatologi; paleontologi; stratigrafi